Level of Science Achievement: Basis for the Production of Strategic Intervention Materials (SIMs) - Verano, Febbie; Comighud, Sheena Mae (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2020)
This research used the descriptive method to determine the level of Science Achievement of Grade VI Pupils: Basis for Production of Strategic Intervention Materials in Bayawan City East Central School, Bayawan City Division during the SY 2019-2020. The quantitative data were gathered from 134 pupils of Bayawan City East Central School, Bayawan City Division during the SY 2019-2020. Also, the researcher conducted a survey questionnaire. Descriptive method was used in this study. The statistical tools used in the analysis of the data were percentage, frequency, mean, weighted mean, and z-test. The study found out that the level of Science Achievement of Grade VI Learners of the Least Learned Organ Systems in terms of the Circulatory System, Respiratory System, and Excretory System were at low mastery level while for the Nervous System, the learners were moving towards mastery stage. Based on the given findings, it served as a basis for the production of Strategic Intervention Materials (SIM) in the different Least Learned Organ Systems namely Circulatory System, Respiratory System, Nervous System, and Excretory System in order to increase the level of learners’ achievement in Science subject.